Iron Contaminated Soils Remediation Using Secondary Metabolites of Trichoderma harzianum T10 and Its Effect on Spinach Growth - Loekas Soesanto; Murti Wisnu Ragil Sastyawan; Endang Mugiastuti; Tamad Tamad (Agrotechnology Research Journal, 2023)
Iron (Fe) is an essential metal whose presence in excess can pollute the environment, cause toxic effects on plants, and degrade soil quality. Efforts have been made to overcome this by remediation using secondary metabolites of Trichoderma harzianum T10. This study aimed to determine the potency and appropriate concentration of T. harzianum T10 secondary metabolites as a remediator for Fe-contaminated soil and its effect on the growth and yield of spinach grown on remediated soil. The research was conducted at the Screen House, Soil Laboratory, and Plant Protection Laboratory, Faculty of Agriculture, Universitas Jenderal Soedirman for four months. A randomized block design was used with treatment consisting of control and secondary metabolites application of T. harzianum T10 concentrations of 25, 50, 75, and 100%, repeated five times. The secondary metabolites were applied in the afternoon by pouring it on the soil in polybags and letting it stand for 10 days in tightly closed conditions. The variables observed were Fe content in the soil, plant height, number of leaves, shoot fresh weight, fresh root weight, and root length of spinach plants. The results showed that the secondary metabolites of T. harzianum T10 have the potential to remediate iron-congested soil. The content of Fe in the soil is 823 ppm. The appropriate concentration of T. harzianum T10 secondary metabolites as a remediator for Fe-contaminated soil is 50%, which can reduce the content of Fe (iron) by 46% compared to controls. The application of T. harzianum T10 secondary metabolites has not affected the growth and yield of spinach, which was grown on remediated soil, although there is a tendency to be better.